(untitled) (Journal Intellectual Sufism Research (JISR), 2026)
This study aims to determine the effect of date content in reducing oxidative stress based on the perspective of hadith and science. The type of method used is Systemic Literature Review (SLR) which is to collect, identify, map, and critically evaluate research results on certain topics. There are 3 stages of the SLR method, namely planning, conducting, and reporting. The results of this study reveal that dates contain antioxidant compounds, namely phenolics, and flavonoids, which can increase antioxidant levels in the body and reduce oxidative stress. This is in accordance with the recommendation of the Prophet Muhammad ﷺ to consume dates as medicine and antidote.